PERTANGGUNGJAWABAN PELAKU USAHA TERHADAP KONSUMEN AKIBAT SALAH DALAM MENAFSIRKAN IKLAN - Rimanda, Fiqri; Syarifudin; Fitri, Sherly Nelsa (Gayaku Publisher, 2023)
The publication is a data mechanism to promote goods to be delivered or offered to the general public or buyers. Specifically, to get the benefits that will be obtained by the maker, this advertisement is expected to provide data and progress that will make people interested in buying their goods. This research uses normative law research through library materials or secondary data by finding a rule of law, legal principles, and legal doctrines to answer the legal issues faced. The answer is that the responsibility of business actors for consumer losses is to provide compensation for damage, pollution, and consumer losses due to consumer goods and or services by the Consumer Protection Act.